Components of book tax differences, corporate social responsibility and equity value - Wei Ling Tye; Nor Shaipah Abdul Wahab (Cogent Business & Management, 2019)
This study examines the relationship between components of book-tax differences (BTD), corporate social responsibility (CSR) and market value of equity in Malaysia. The sources that impact BTD are unclear as previous studies incline to focus on aggregated BTD. By analysing the data of 373 Malaysian non-financial public-listed companies from 2008 to 2015 using balanced-panel regression models, the findings provide evidence on shareholders' valuation of permanent and temporary differences in the presence of CSR. Consistent with legitimacy theory, in which companies are theorised to conduct activities to appear legitimate in the eye of the shareholders, CSR is found to affect equity value positively. This suggests that the companies achieve their objectives to appear legitimate through CRS activities. As permanent differences and temporary differences imply the extent of companies' tax planning activities through strategic and deferral tax planning, this study finds negative relationship between permanent differences and temporary differences, and equity value. This suggests that the shareholders are reluctant to incrementally value tax planning activities through permanent differences and temporary differences due to the activities' inherent risk. In addition, this study finds shareholders simultaneously and positively value permanent and temporary differences, when CSR and the BTD components interact, suggesting that the strength of the initial relationships between permanent differences, temporary differences and equity value are depending on the company's CSR engagement.
Keywords: 650; book tax differences; corporate social responsibility; equity value; permanent differences; statutory tax rates differences; temporary differences